Forkhead box O1 in metabolic dysfunction-associated fatty liver disease: molecular mechanisms and drug research - Sha, Xiangjun; Zou, Xinlei; Liu, Sidi; Guan, Canghai; Shi, Wujiang; Gao, Jianjun; Zhong, Xiangyu; Jiang, Xingming (Frontiers in Nutrition, 2024)
Metabolic associated fatty liver disease (MAFLD) is a chronic liver disease that progresses from hepatic steatosis to non-alcoholic steatohepatitis, cirrhosis, and liver cancer, posing a huge burden on human health. Existing research has confirmed that forkhead box O1 (FOXO1), as a member of the FOXO transcription factor family, is upregulated in MAFLD. Its activity is closely related to nuclear-cytoplasmic shuttling and various post-translational modifications including phosphorylation, acetylation, and methylation. FOXO1 mediates the progression of MAFLD by regulating glucose metabolism, lipid metabolism, insulin resistance, oxidative stress, hepatic fibrosis, hepatocyte autophagy, apoptosis, and immune inflammation. This article elaborates on the regulatory role of FOXO1 in MAFLD, providing a summary and new insights for the current status of drug research and targeted therapies for MAFLD.